Molecular fingerprinting of dabai (Canarium odontophyllum Miq.) progenies (half-sib family) Using DAMD Markers - Jong, Linda Wang Yng (Universiti Malaysia Sarawak, UNIMAS, 2010)
Molecular fingerprinting of Dabai or Canarium odontophyllum was carried out using the Directed Amplification of Minisatellite Region DNA (DAMD) marker. Three primers, namely 33.6, M13 and the YNZ22 were selected to determine the genetic relatedness between the dabai progenies (half-sib family) and its maternal genotype as these primers are capable of producing informative and repeatable outcome. A total of 51 loci were generated to evaluate the genetic relatedness of the dabai progenies collected from Sarikei. The binary data matrix based on Jaccard’s coefficient matrix was calculated and dendrogram was constructed using unweighted pair group mean average (UPGMA). Two major clusters were constructed and all the dabai progenies were grouped as cluster I and the mother tree in cluster II and both the clusters were closely related. In addition, the neighbor-joining tree constructed based on DSA share allele showed similar result as UPGMA dendrogram showing close relationship among dabai progenies and maternal tree. Besides, the calculation based on Jaccard’s coefficient matrix shown the average similarity of 0.77 using combination of all the 3 primers. This figure supported the fact that the breeding mechanism for dabai is via cross pollination, thus eliminate the possibility of self-pollination as none of the the progeny is identical to its siblings.